Fanniidae (Diptera): new species, new records and first description of the male of Fannia latifrontalis Hennig - Barták, Miroslav; Preisler, Jiří; Kanavalová, Liliana; Kubík, Štěpán (Zootaxa, 2021)
Fannia bohemica sp. nov. (Czech Republic, Slovakia) is described and illustrated. Male of F. latifrontalis Hennig, 1955 is described and illustrated for the first time. Fannia jezoensis Nishida, 1976 is first reported from West Palaearctic, Fannia morrisoni Malloch, 1913 is first recorded from Palaearctic Region. Fannia umbrosa (Stein, 1895) and F. armata (Meigen, 1826; first record based on morphologically identified specimens) are new records from Nearctic Region. Six species (Fannia fuscitibia Stein, 1920, F. latifrontalis, F. limbata (Tiensuu, 1938), F. verrallii (Meade, 1891), F. gotlandica Ringdahl, 1926 and F. spathiophora, Malloch, 1918) are recorded for the first time from Slovakia.